2007
DOI: 10.1139/w07-099
|View full text |Cite
|
Sign up to set email alerts
|

ACC deaminase from plant growth-promoting bacteria affects crown gall development

Abstract: In addition to the well-known roles of indoleacetic acid and cytokinin in crown gall formation, the plant hormone ethylene also plays an important role in this process. Many plant growth-promoting bacteria (PGPB) encode the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase, which can degrade ACC, the immediate precursor of ethylene in plants, to alpha-ketobutyrate and ammonia and thereby lower plant ethylene levels. To study the effect of ACC deaminase on crown gall development, an ACC deaminase gene fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…Similar results have been obtained with castor bean and tomato plants infected by Agrobacterium tumefaciens. While P. putida UW4 was able to decrease crown gall formation and subsequent damage and loss of plant biomass, the acdS knockout mutant had no significant impact on protecting tomato plants from the A. tumefaciens infection (Hao et al 2007;Toklikishvili et al 2010). These results suggest that ACC deaminase activity, and the consequent lowering of deleterious plant ethylene levels, is the mechanism responsible for P. putida UW4 plant growth promotion activity as well as its ability to protect plants against biotic as well as abiotic stress (Grichko et al 2000;Wang et al 2000;Cheng et al 2007;Glick et al 2007;Hao et al 2007;Gamalero et al 2010;Toklikishvili et al 2010).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar results have been obtained with castor bean and tomato plants infected by Agrobacterium tumefaciens. While P. putida UW4 was able to decrease crown gall formation and subsequent damage and loss of plant biomass, the acdS knockout mutant had no significant impact on protecting tomato plants from the A. tumefaciens infection (Hao et al 2007;Toklikishvili et al 2010). These results suggest that ACC deaminase activity, and the consequent lowering of deleterious plant ethylene levels, is the mechanism responsible for P. putida UW4 plant growth promotion activity as well as its ability to protect plants against biotic as well as abiotic stress (Grichko et al 2000;Wang et al 2000;Cheng et al 2007;Glick et al 2007;Hao et al 2007;Gamalero et al 2010;Toklikishvili et al 2010).…”
Section: Discussionmentioning
confidence: 93%
“…While P. putida UW4 was able to decrease crown gall formation and subsequent damage and loss of plant biomass, the acdS knockout mutant had no significant impact on protecting tomato plants from the A. tumefaciens infection (Hao et al 2007;Toklikishvili et al 2010). These results suggest that ACC deaminase activity, and the consequent lowering of deleterious plant ethylene levels, is the mechanism responsible for P. putida UW4 plant growth promotion activity as well as its ability to protect plants against biotic as well as abiotic stress (Grichko et al 2000;Wang et al 2000;Cheng et al 2007;Glick et al 2007;Hao et al 2007;Gamalero et al 2010;Toklikishvili et al 2010). In addition, it has been previously demonstrated that transgenic plants that express a bacterial acdS gene under the control of a root specific promoter are more resistant to pathogen induced stress as well as abiotic stress caused by salt, flooding and metals (Robison et al 2001a, b;Grichko and Glick 2001;Grichko et al 2000;Stearns et al 2005;Sergeeva et al 2006).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Next, the cells were collected by centrifugation at 6,000g for 10 min at 4°C, rinsed twice with M9 minimal salts (without a nitrogen source), and subsequently resuspended in 10 ml of modified M9 minimal medium with 5 mM ACC and incubated at 200 rpm for 40 h at 28°C with shaking as described by Hao et al (2007). The ACC deaminase activity was measured in bacterial extracts prepared as described by Penrose and Glick (2003) and determined by measuring the production of a-ketobutyrate using a standard curve of the substrate between 0.1 to 1 lM (Honma and Shimomura 1978).…”
Section: Seeds and Bacteriamentioning
confidence: 99%
“…The plant growth promoting effects of ACC deaminase may be most effective during pathogen attack [94,[170][171][172] and in stressful environments (e.g., flooded and heavy-metal contaminated soils) [173,174]. Additionally, under stress conditions plant vitamin synthesis declines.…”
Section: Modern Approaches To Agriculture Management-utilization Of Pmentioning
confidence: 99%